2010
DOI: 10.1134/s0006297910080018
|View full text |Cite
|
Sign up to set email alerts
|

Renalase, a new secretory enzyme responsible for selective degradation of catecholamines: Achievements and unsolved problems

Abstract: Renalase is a recently discovered secretory enzyme responsible for selective degradation of blood catecholamines. The review summarizes literature data on expression of this enzyme and on its structure and functions. Special attention is paid to unsolved and questionable problems including: 1) prediction of the presence of FAD in the protein structure based on amino acid sequence similarity of renalase with known FAD-dependent enzymes; 2) identity of plasma and urinary renalase; 3) mechanism underlying convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 42 publications
0
21
0
2
Order By: Relevance
“…They even concluded that it is unlikely that renalase is a catecholamine-metabolizing enzyme; it may have important cardiovascular functions, but through another mechanism. The same doubts were recently presented by Medvedev and biochemist colleagues (11). On the other hand, Luft (12), according to studies quoted by him, noted that dopamine is associated with lower BP and cardiovascular risk, which is why diminishing dopaminergic tone (prompted by renalase, for example) would increase BP and cardiovascular risk.…”
Section: Discussionmentioning
confidence: 75%
“…They even concluded that it is unlikely that renalase is a catecholamine-metabolizing enzyme; it may have important cardiovascular functions, but through another mechanism. The same doubts were recently presented by Medvedev and biochemist colleagues (11). On the other hand, Luft (12), according to studies quoted by him, noted that dopamine is associated with lower BP and cardiovascular risk, which is why diminishing dopaminergic tone (prompted by renalase, for example) would increase BP and cardiovascular risk.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, in their recent paper, Milani et al [16] pointed out that renalase was not a monoamine oxidase and most probably not an oxidase. Due to the growing criticism on potential monoamine oxidase activity and structure of renalase [15,16,17], interpretation of data on renalase activity is rather difficult. Xu et al [6] assessed renalase expression, whereas in our study we measured renalase level using a commercially available assay.…”
Section: Discussionmentioning
confidence: 99%
“…This is an inconsistent observation, since it has long been known that FMN or FAD biosynthesis by E. coli is not a limiting factor in flavoprotein production, even when expression levels exceed 25 mg of target protein per gram of bacterial cells [38,39]. Indeed, Medvedev and coauthors clearly stated that a conclusive proof that renalase contains FAD was still lacking [9]. This proof was obtained in the same year, when after several expression trials in both E. coli [40] and Saccharomyces cerevisiae [Aliverti, unpublished results], we finally obtained limited amounts of highly purified human flavin-containing renalase spontaneously folded in vivo in the bacterial host [40].…”
Section: Purification Of Endogenous and Recombinant Renalase Formsmentioning
confidence: 99%
“…While the link between renalase and the pathophysiology of the cardiovascular system seems now to be clear, the molecular mechanism underlying its actions is still obscure in most respects. Several excellent reviews have recently been published on the consequences of renalase deficiency in diabetes, hypertension, cardiac hypertrophy, myocardial ischemia, and stroke [8][9][10][11][12][13]. This article will mainly focus on the molecular and biochemical properties of mammalian renalase through a critical survey of the often contradictory results published to date on the possible catalytic properties of this protein, with the purpose of discriminating between solid achievements and the many inconsistent observations.…”
Section: Introductionmentioning
confidence: 99%